"Establishing the Conservative Phenomenon". Issue 3 (3rd July 2019) - Merriman, Ben
ABSTRACT: Political events since 2016 have prompted rapidly growing sociological interest in varieties of conservative, populist, and nationalist politics. This article lays out an initial challenge for studying these varieties of politics effectively: the discipline's knowledge of conservatism is relatively limited, but members of the discipline possess strong beliefs and opinions about the phenomenon, and are regular consumers of media accounts that commonly rely upon doubtful or unsociological assumptions. The article presents a brief overview of work still to be done. It then discusses common habits of mind that may produce explanations that are incomplete or asymmetric – that is, explanations that account for right-leaning political sentiments or activities using categories essentially distinct from those commonly used to explain left-leaning analogues. The article concludes by discussing several viable approaches to explaining political conservatism and related phenomena.